Cooperation on Readmission in the Euro-Mediterranean Area and Beyond: Lessons Learned and Unlearned - (:unkn) unknown (My University, 2023)
The three contributions contained in this study have opted to go beyond the recurrent reference to reluctance and uncooperativeness by shedding light on the agency of non-EU countries located in the Southern Mediterranean and in Africa. They interrogate the various consequences of cooperation on readmission as well as the factors that have fed into the expansion of a system having detrimental implications for human rights observance and states’ accountability, as well as unintended effects on international cooperation.The common denominator shared by the authors lies in questioning the disproportionate policy attention to leverage, operability and effectiveness when addressing cooperation on readmission with non-EU countries. They propose rethinking the boundaries of the problem by emphasising that asymmetrical patterns of cooperation on readmission are not only based on unequal costs and benefits. Despite their asymmetry, they also remain meaningful for the state actors involved. This is a fact that has significantly shaped the relations between Southern Mediterranean countries and their European counterparts as well as between Southern Mediterranean countries and their African counterparts. Consequently, we need to bear in mind this grammar. Sometimes, interactions can be conducive to reinforced interdependence, which, in turn, can lead to new unintended consequences and challenges. As shown in this study, cooperation on readmission in the Mediterranean and African contexts is a case in point.
Keywords: African Research